Tacit Knowledge Sharing for Individual Innovation Capability at Indonesian SMI - Rumanti, Augustina Asih (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
Knowledge sharing is an asset for industrial organizations. These assets play a key role in global competition. Especially in increasing the innovation capacity of Small and Medium Industries (IKM). In this case innovation means introducing new products, making qualitative changes to existing products, introducing new processes in industrial organizations, creating new markets, and developing new sources of raw materials or other inputs. Much knowledge is stored in individuals, which is called tacit knowledge. Sharing tacit knowledge among individuals associated with industry organizations can increase the capacity of innovation previously explained. This study analyzes the relationship between sharing tacit knowledge and organizational innovation capabilities. Certain SMI employees located in Semarang, Central Java were the respondents for this study. Opinions as many as 45 members of each IKM have been analyzed using the hypothesis testing method. Through this research, it is shown that the level of sharing of tacit knowledge influences IKM's innovation ability.